Electrical Indication of Modified Concrete´s and Mortar´s Ability Resist Chloride Ion Penetration - Torrado-Gómez, Luz Marina; Solarte-Vanegas, Norma Cristina (Lámpsakos (revista descontinuada), 2017)
This article describes the ability of concrete and mortar mixtures with different fly ash contents to resist chloride ion penetration 14 and 28 days after casting. The Rapid Chloride Permeability Test (RCPT) in accordance to the norm ASTM C1202 was used in order to obtain qualitative indications of the chloride ion penetrability depending on the electrical conductance of concrete respectively mortar samples. Furthermore, the Automatic Concrete Water Permeability Apparatus at Four Cells C430X from Matest was used to measure the water permeability 28 days after casting. Finally, the uniaxial compressive strength was measured 28 days after casting. The following conclusions can be made. The results of the Chloride Permeability Test (RCPT) did not show a clear correlation between the ash content, the a/c ratio and the Chloride Ion Penetrability. However, the chloride diffusion coefficient for the hormone and mortar at 28 days tends to increase with increasing a / c ratio and decreases with the age of hydration. As for permeability, an increase in the permeability was found at 28 days of age with an increasing ratio of a/c ratio.